Crossing Central Europe : Continuities and Transformations, 1900 and 2000 - Smith, Carrie, 1975-; Mitterbauer, Helga (Book collections on Project MUSE., 2017)
"Crossing Central Europe is a pioneering volume that focuses on the complex networks of transcultural interrelations in Central Europe from 1900 to 2000. Scholars from Canada, the United States, and Europe identify the motifs, topics, and ways of artistic creation that define this cross-cultural region. This interdisciplinary volume is divided into two historical periods and includes analyses of literature, film, music, architecture, and media. By focusing first on the interrelations in the nineteenth and early twentieth-century, the contributors reveal a complex trans-ethnic network at play that disseminated aesthetic ideals. This network continued to be a force of aesthetic influence leading into the twenty-first century despite globalization and the influence of mass media. Helga Mitterbauer and Carrie Smith-Prei have embarked on a study of the overlapping artistic influences that have outlasted both the National Socialist regime and the Cold War."--